2023
DOI: 10.1210/endrev/bnad005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF Axis and the Receptor for Advanced Glycation End Products: Role in Meta-inflammation and Potential in Cancer Therapy

Abstract: In metabolic conditions such as obesity and diabetes, which are associated with deregulated signaling of the Insulin/IGF system (IIGFs), inflammation plays a dominant role. In cancer, IIGFs is implicated in disease progression, particularly during obesity and diabetes, however further mediators may act in concert with IIGFs to trigger meta-inflammation. The receptor for advanced glycation end-products (RAGE) and its ligands bridge together metabolism and inflammation in obesity, diabetes and cancer. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 358 publications
0
16
0
Order By: Relevance
“…A higher expression of RAGE is associated with obesity, inflammation and cancer. Interestingly, a bidirectional regulation between both IR/IGF1R and RAGE has been suggested [73], and, consistently, studies have shown that CR reduces soluble RAGE and advanced glycation end products [98,99]; therefore, further studies will consider investigating the relationship between CR, miR-15b and RAGE in mammary tumors. Expanding on these mechanisms will support our results that miR-15b functions as a tumor suppressor in TNBC, which is in accordance with other reports illustrating the tumor-suppressive, antiproliferative functions of miR-15b in ovarian cancer, glioblastoma cells, and breast cancer stem cells [34,87,88].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A higher expression of RAGE is associated with obesity, inflammation and cancer. Interestingly, a bidirectional regulation between both IR/IGF1R and RAGE has been suggested [73], and, consistently, studies have shown that CR reduces soluble RAGE and advanced glycation end products [98,99]; therefore, further studies will consider investigating the relationship between CR, miR-15b and RAGE in mammary tumors. Expanding on these mechanisms will support our results that miR-15b functions as a tumor suppressor in TNBC, which is in accordance with other reports illustrating the tumor-suppressive, antiproliferative functions of miR-15b in ovarian cancer, glioblastoma cells, and breast cancer stem cells [34,87,88].…”
Section: Discussionmentioning
confidence: 98%
“…In pathological conditions, such as metabolic syndrome and obesity, an excess of body fat is associated with increased risk of several cancers, including breast cancer [2,3,71]. The underlying mechanism driving the obesity-breast cancer link are not fully understood, but obesity-associated alterations [72], including hyperinsulinemia and increased availability of IGF1, are associated with increased cell proliferation, migration and metastasis, insensitivity to antigrowth signals, induction of angiogenesis, and exacerbating the adipose-tissuemediated chronic inflammation [73]. Multiple studies have shown that the protective effect of CR in cancer progression are associated with its regulation of IGF1R signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The combined effect of obesity and diabetes on breast cancer outcomes has been extensively reported in humans [21][22][23]37], and undiagnosed IGT is known to affect the survival of breast cancer patients [38]. Insulin/IGF signaling is reported to be dysregulated in obesity, diabetes, and breast cancer underscoring intricate overlaps in the underlying metabolic abnormalities and disease spectrum [39]. Hence, in this study, we investigated the combined effects of obesity and IGT on breast cancer risk and probable mechanisms using a genetically obese rat model with IGT for chemically induced breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since its discovery, it has been the subject of extensive research due to its implications in several diseases associated with chronic inflammation upon its activation by damageassociated molecular patterns (DAMPs). [16] In vitro and in vivo studies have shown the potential of RAGE as a therapeutic target in neurodegeneration, [19][20][21] cancer, [22][23] and metabolic diseases such as cardiovascular diseases, [24] or obesity. [25] Therefore, the discovery of an efficient ligand which can inhibit RAGE has been pursued as a pathway to control the effects from over-stimulated RAGE-mediated inflammation observed in these disorders.…”
Section: Introductionmentioning
confidence: 99%